The Role of Employee Engagement in Mediating Perceived Organizational Support for Millennial Employee Organizational Citizenship Behavior - Ellen Priskila; Melitina Tecoalu; Saparso; Hery Winoto Tj (Syntax Corporation Indonesia, 2021)
The era of globalization is a time when competition becomes increasingly tight, employees are required to be able to show extra work behavior that can exceed the expectations of the organization (extra role behavior). The existence of high initiative from employees is able to improve the effectiveness of an organization, while employees who have good organizational support will also form positive behavior as a form of reciprocal support to the organization. Through employee engagement is expected to strengthen the behavior of the organization's citizenship. In Indonesia is currently entering the era of demographic bonuses, the condition makes this research interesting to do in millennials. The purpose of this study is to test the influence of employee engagement in mediating perceived organizational support to the organizational citizenship behavior of 83 millennial employees of PT Tatalogam Lestari. Structural Equation Modelling (SEM) analysis techniques using SmartPLS were used in this study. The results of the analysis stated that there is an influence perceived organizational support, employee engagement and organizational citizenship behavior. Employee engagement is also proven to mediate the influence of perceived organizational support on organizational citizenship behavior. This study found that the higher the perception of organizational support in employees, the higher the sense of attachment of employees with the organization, so as to encourage the occurrence of organizational citizenship behavior in employees.